2022
DOI: 10.1186/s13041-022-00922-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cdk5 activating subunit p35 in synaptic plasticity in excitatory and inhibitory neurons

Abstract: Cyclin-dependent kinase 5 (Cdk5) /p35 is involved in many developmental processes of the central nervous system. Cdk5/p35 is also implicated in synaptic plasticity, learning and memory. Several lines of conditional Cdk5 knockout mice (KO) have been generated and have shown different outcomes for learning and memory. Here, we present our analysis of p35 conditional KO mice (p35cKO) in hippocampal pyramidal neurons or forebrain GABAergic neurons using electrophysiological and behavioral methods. In the fear cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Thus, nNOS also promotes the S-nitrosylation of p35 leading to its ubiquitin/proteasome-dependent degradation, which also can indirectly impact CDK5 activity [ 282 ]. In this sense, using p35 conditional KO mice (p35cKO) in hippocampal pyramidal neurons, showed that CDK5/p35 in excitatory neurons is important for hippocampal synaptic plasticity and associative aversive memory retention [ 283 ]. Therefore, the regulation of CDK5 by nNOS may be directly implicated in the consequences of stress in the BLA-hippocampus pathway, contributing to the persistence of aversive memory.…”
Section: Nnos No-related Mechanisms and Stress Responsementioning
confidence: 99%
“…Thus, nNOS also promotes the S-nitrosylation of p35 leading to its ubiquitin/proteasome-dependent degradation, which also can indirectly impact CDK5 activity [ 282 ]. In this sense, using p35 conditional KO mice (p35cKO) in hippocampal pyramidal neurons, showed that CDK5/p35 in excitatory neurons is important for hippocampal synaptic plasticity and associative aversive memory retention [ 283 ]. Therefore, the regulation of CDK5 by nNOS may be directly implicated in the consequences of stress in the BLA-hippocampus pathway, contributing to the persistence of aversive memory.…”
Section: Nnos No-related Mechanisms and Stress Responsementioning
confidence: 99%
“…Cyclin-dependent kinase 5 (Cdk5) is a proline-directed serine/threonine kinase, which is a unique component of the family of cyclin-dependent kinases (Dhavan and Tsai, 2001 ; Malumbres, 2014 ). Cdk5 plays a pivotal role in the nervous system, including cortex layer formation, synaptic growth and maturation, synaptic vesicular transport (Liu et al, 2022 ; Takahashi et al, 2022a ), stress-enhanced memory consolidation, dendritic spine formation, neuronal migration and differentiation, neurite outgrowth and length (Chen et al, 2017 ; Huang et al, 2017 ; Shinmyo et al, 2017 ; Lee et al, 2018 ; Nishino et al, 2019 ; Rao et al, 2020 ; Im et al, 2022 ), learning and long-term behavioral changes, axonal regeneration (Xu et al, 2017 ; Hwang and Namgung, 2021 ), brain microtubule network and actin cytoskeleton remodeling (Shah and Lahiri, 2017 ; Shah and Rossie, 2018 ), as well as normal cerebellar development and functions (Lee et al, 2019 ; Li et al, 2019 ; Kodani et al, 2020 ; Ouyang et al, 2020 ). Additionally, Cdk5 also plays a key role in gene expression, cell differentiation, angiogenesis, and aging (Arif, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although loss of 39 is not lethal, it attenuates overall Cdk5 activity in neurons as well as leads to aberrant axonal growth and impaired dendritic spine formation through affecting Cdk5 targets governing neuronal differentiation and network formation ( Li et al, 2016 ). In adult brain, emerging evidences have indicated that Cdk5 complex regulated multiple neuronal functions including neuronal survival, neurite and axon outgrowth, synaptic plasticity, neurotransmission ( Ye et al, 2014 ; Sasamoto et al, 2017 ; Takahashi et al, 2022 ). Because of its extensive and crucial roles in nervous system, the dysfunction of Cdk5 is critically involved in numerous neurological disorders such as neurodegenerative diseases, stroke, psychiatric disorders, pathological pain, epilepsy and so on.…”
Section: Introductionmentioning
confidence: 99%